The Contemporary Elegy in World Literature - Bardazzi, Adele,; Binetti, Roberto,; Culler, Jonathan, (DQR Studies in the Lyric ;, 2025)
This volume navigates the entangled expressions of mourning across languages, cultures, and traditions, shedding light on the evolving shapes and discourses of contemporary elegy in world literature. By adopting a transnational approach, this collection offers a much needed conceptualization of what elegy has become today. Contributors are Nick Admussen, Adele Bardazzi, Roberto Binetti, Emily Drumsta, Francesco Giusti, Roberto Gaudioso, Gail Holst-Warhaft, Karen Leeder, Brandon Menke, Jahan Ramazani, Rachel Elizabeth Robinson, David Sherman and Ivanna Sang Een Yi.